MicroRNAs and long non-coding RNAs as novel regulators of ribosome biogenesis - McCool, Mason A. (Biochem Soc Trans, 2020)
Ribosome biogenesis is the fine-tuned, essential process that generates mature ribosomal subunits and ultimately enables all protein synthesis within a cell. Novel regulators of ribosome biogenesis continue to be discovered in higher eukaryotes. While many known regulatory factors are proteins or small nucleolar ribonucleoproteins, microRNAs (miRNAs), and long non-coding RNAs (lncRNAs) are emerging as a novel modulatory layer controlling ribosome production. Here, we summarize work uncovering non-coding RNAs (ncRNAs) as novel regulators of ribosome biogenesis and highlight their links to diseases of defective ribosome biogenesis. It is still unclear how many miRNAs or lncRNAs are involved in phenotypic or pathological disease outcomes caused by impaired ribosome production, as in the ribosomopathies, or by increased ribosome production, as in cancer. In time, we hypothesize that many more ncRNA regulators of ribosome biogenesis will be discovered, which will be followed by an effort to establish connections between disease pathologies and the molecular mechanisms of this additional layer of ribosome biogenesis control.